Keanekaragaman dan komposisi spesies laba-laba predator dan parasitoid Hymenoptera pada tanaman jagung dengan dan tanpa refugia pada musim yang berbeda: Diversity and species composition of predatory spiders and Hymenopteran parasitoid on maize fields with and without refugia in different seasons - Sulthoni, Fahmi; Tarno, Hagus; Rizali, Akhmad; Priawandiputra, Windra; Buchori, Damayanti; Johannis, Midzon (Jurnal Entomologi Indonesia, 2023)
Refugia are plants that play an important role in the conservation of natural enemies in agroecosystem. Refugia plants are useful for providing shelter and host/prey for natural enemies, especially parasitoids and predators. This study was aimed to investigate the effect of refugia and different planting seasons on the diversity and species composition of natural enemies (especially predatory spiders and Hymenoptera parasitoids) in maize fields. Field research was conducted in two different seasons i.e., dry season (April to July 2022) and rainy season (September to December 2022) in Tumpang Village, Malang District. The maize fields for the study were grouped into four different areas, with two observation plots (size 40 m í— 50 m) in each area, consisting of a monoculture maize field (control plot) and a maize field with refugia plants (treatment plot). Sampling was conducted using pitfall traps (for predatory spiders) and yellow traps (for Hymenoptera parasitoids). Traps were set for 1 í— 24 hours and conducted at 2, 4, 6, 8, 10 and 12 weeks after planting. The results from two planting seasons were obtained predatory spider diversity amounted to 626 individuals consisting of 7 families, and 40 morphospecies, while Hymenoptera parasitoids amounted to 787 individuals consisting of 5 families, and 63 morphospecies. Based on generalized linear models analysis, it was found that refugia planting did not affect the diversity of natural enemies, but affected the species composition of predatory spiders. Different planting seasons affect the diversity and species composition of predatory spiders as well as Hymenoptera parasitoids.